2012
DOI: 10.1038/npp.2012.265
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing Effects Of Compounds Lacking Intrinsic Efficacy At α1 Subunit-Containing GABAA Receptor Subtypes in Midazolam- But Not Cocaine-Experienced Rhesus Monkeys

Abstract: Benzodiazepines are prescribed widely but their utility is limited by unwanted side effects, including abuse potential. The mechanisms underlying the abuse-related effects of benzodiazepines are not well understood, although a1 subunit-containing GABA A receptors have been proposed to have a critical role. Here, we examine the reinforcing effects of several compounds that vary with respect to intrinsic efficacy at a2, a3, and a5 subunit-containing GABA A receptors but lack efficacy at a1 subunit-containing GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
2
30
1
Order By: Relevance
“…Regarding α3GABA A receptors, the imidazopyridine compound TP003 has been recognized as the primary research tool used for exploring the function of this receptor subtype (Fischer et al, 2011; Marowski et al, 2012; Shinday et al, 2013). TP003 has been described as having comparatively high agonist efficacy at α3GABA A receptors but essentially no efficacy at α1GABA A , α2GABA A , and α5GABA A receptors (Dias et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding α3GABA A receptors, the imidazopyridine compound TP003 has been recognized as the primary research tool used for exploring the function of this receptor subtype (Fischer et al, 2011; Marowski et al, 2012; Shinday et al, 2013). TP003 has been described as having comparatively high agonist efficacy at α3GABA A receptors but essentially no efficacy at α1GABA A , α2GABA A , and α5GABA A receptors (Dias et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…And activated IL-6 receptor recruits JAK1, JAK2, and Tyk2 tyrosine kinases which can phosphorylate STAT1 and STAT3 [18,19]. Midazolam is a potent benzodiazepine derivative with powerful hypnotic, sedative, anxiolytic, amnestic, anticonvulsant and muscle-relaxant properties by modulating the GABA A receptor in the central nervous system [20] . Recent study has demonstrated that astrocytic activation, maturation, and differentiation are involved in the expression of central type benzodiazepine receptors coupled to GABA A receptors in astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…While strong conclusions are precluded because of the underpowered regression analyses (and consequent lack of statistical significance), these findings raise the possibility that the binding sites that 3-PBC, βCCT and flumazenil antagonized were more likely to be the α2-and/or α3GABA A receptor sites than either α1- or α5GABA A sites. This possibility is bolstered by our previous work with subtype-selective agonists, which implicated the α3GABA A , and potentially the α2GABA A , receptor subtype in the reinforcing effects of benzodiazepines (Rowlett et al, 2005; Shinday et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Monkeys were trained to self-administer the benzodiazepine midazolam (0.03 mg/kg/infusion) under a PR schedule of i.v. drug injection (Shinday et al, 2013). At the beginning of each session, a set of two white stimulus lights above a response lever was illuminated (Med Associates, St Albans, VT).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation